Distribution and function of hyaluronan binding protein involved in hyaluronan depolymerization (HYBID, KIAA1199) in the mouse central nervous system. (7th April 2017) - Yoshino, Yuta; Ishisaka, Mitsue; Tsuruma, Kazuhiro; Shimazawa, Masamitsu; Yoshida, Hiroyuki; Inoue, Shintaro; Shimoda, Masayuki; Okada, Yasunori; Hara, Hideaki
Highlights: Hybid mRNA expresses in granular cell layer of the murine hippocampus and cerebellum. Hybid KO mice show memory impairment. Hippocampal HA of Hybid KO mice increased in the average molecular mass as well as the total amount. Abstract: HYBID ( HY aluronan B inding Protein I nvolved in hyaluronan [HA] D epolymerization, KIAA1199) is one of the HA binding proteins that is involved in the depolymerization of HA. HYBID mRNA is highly expressed in the brain, however, the role of HYBID in the brain remains unclear. In this study, we bred Hybid knock-out (KO) mice and evaluated the function of Hybid in the central nervous system. Hybid mRNA was expressed in the brain, especially in the hippocampus and cerebellum, in wild-type mice. Hybid KO mice demonstrated decreased mnemonic ability in novel object recognition and Morris water maze tests. The average molecular mass of hippocampal HA increased in KO mice, accompanied by a significant increase in the total HA amount. Hybid KO mice did not differ in behavior from wild-type mice in the open field test, evaluation of acoustic startle responses, or drug-induced seizure test. In real-time PCR, Hyal1 and Hyal2 mRNA levels, which code hyaluronidases 1 and 2, respectively, did not differ between the Hybid KO and wild-type mouse brain. These results indicate that Hybid plays a key role in memory function in the brain.